Land-cover changes and influences on playa wetland inundation on the Southern High Plains. (April 2020) - Starr, Scott M.; McIntyre, Nancy E.
Abstract: Playas are ephemeral, depressional wetlands that are the primary form of surface water in the Southern High Plains of North America, an area that has experienced extensive and relatively recent land-cover changes. Because the influences of these changes in landscape structure (composition, configuration, and connectivity of land-cover types) on playas have not been assessed over time, we used remotely sensed imagery to quantify changes in the five regionally dominant land-cover categories (cropland, rangeland/grassland, fallow, developed, and water) and playa inundation patterns in Texas on six dates during the late growing season over a 23-year span (1986–2008). A decrease in the number of wet playas was observed over that time, associated with significant differences among land covers between and within years around dry vs. wet playas (with playas surrounded by rangeland/grassland being twice as likely to be dry than playas surrounded by cropland). Mean patch size and overall area of rangeland/grassland increased over time, possibly due in part to conservation efforts in the area. Because playas are crucial habitats, these landscape changes have likely affected regional biodiversity; our findings indicate that assessments of the remaining playa wetlands should be undertaken to compare biotic communities with surrounding land-cover history. Graphical abstract: Image 1 Highlights: The occurrence of water in playas was associated with regional land use, 1986–2008. Mean patch size and overall area of rangeland/grassland increased over time. Playas surrounded by rangeland/grassland were twice as likely to be dry. The number of playas that held water decreased over time.